Pomodoro Pro: a gamified time management mobile application - Abdullah Zawawi, Suhailah; Zahid, Nur Adlin; Zainal Azmi, Nurazlin (KICT Publishing, IIUM, 2025)
Pomodoro Pro is a gamified time management mobile application designed to enhance students' productivity and academic success. The introduction outlines the challenges students face with procrastination and ineffective time tracking, emphasising the need for an engaging and integrated solution. A literature review highlights gaps in existing tools, such as Boosted Time Tracker and Habitica, particularly in terms of motivation and collaboration features. The agile methodology guides development, incorporating user feedback from surveys to inform the design of features such as task management, calendar tracking, and group collaboration. Results indicate improved time management and engagement, with the incorporation of gamified elements fostering increased motivation. Additionally, Pomodoro Pro offers an efficient and user-friendly tool for both academic and personal productivity.